Constructing a Data Mining Model using Fuzzy Decision Tree - Vijay Kumar, HemlataAggarwal, H.D. Arora (International Journal of Advanced Science and Technology, 2020)
Data Mining is a very useful concept to deal with a huge amount of data in the real world. In the real world we are dealing with not only complex and multi-dimensional data set, but also with uncertain and incomplete data sets. Data mining provides many algorithms and tools to discover interesting and useful patterns from the structured and unstructured data. In this paper we discuss data mining techniques and decision tree algorithm. We apply decision tree algorithm to construct a decision tree from the structured data set using fuzzy set theory and entropy. We construct a fuzzy decision tree for fuzzy data for which numerical value of attributes are defined by trapezoidal fuzzy numbers, crisp value as well as interval value. This paper also presents an application of data mining to solve a decision-making problem. We also discuss the construction rule for a problem from fuzzy decision tree.